Statistical Fragility of Findings From Randomized Phase 3 Trials in Pediatric Oncology - Hannah E. Olsen; Pei‐Chi Kao; Caleb Richmond; David S. Shulman; Wendy B. London; Steven G. DuBois (Cancer Medicine)
ABSTRACT Purpose The fragility index (FI) is an adjunctive metric to facilitate the interpretation of p‐values in clinical trials. The FI has not been studied in phase 3 trials in pediatric oncology. Methods PubMed was used to identify phase 3 pediatric oncology trials published between 1980 and 2020. We report trial characteristics and calculate the FI for trials with a binary outcome and survival‐inferred fragility index (SIFI) for trials with a time‐to‐event outcome. FI/SIFI is the number of patients from one arm of a trial who would need to change groups for the statistical conclusion to change. We also report fragility quotients (FQ and SFQ) to normalize FI and SIFI relative to trial size. Results One hundred and thirteen trials included sufficient data for analysis. The median FI for trials with a binary outcome (n = 40) was 4.5 (range: 1–33). The median SIFI for trials with a time‐to‐event outcome (n = 73) was 13 (range: 0–61). The FI or SIFI was less than the number of patients lost to follow‐up in 25% of 36 trials. Median FQ and SFQ were 0.026 and 0.03, respectively, and did not significantly vary according to trial characteristics. While sample sizes increased over time, the FQ and SFQ remained stable. Conclusions The statistical conclusions of pediatric oncology phase 3 trials hinge on a relatively small number and proportion of patients. Despite the sample size limitations of low prevalence diseases, pediatric cancer trials are similarly or less fragile than adult oncology trials. Smaller trials do not appear more statistically fragile than larger trials. Statistical fragility appears to have remained constant over the four decades evaluated. We recommend reporting FI or SIFI, in conjunction with p‐values, for all phase 3 pediatric oncology trials.